PTPRT epigenetic silencing defines lung cancer with STAT3 activation and can direct STAT3 targeted therapies. Issue 6 (2nd July 2020) - Sen, Malabika; Kindsfather, Audrey; Danilova, Ludmila; Zhang, Feng; Colombo, Raffaele; LaPorte, Matthew G.; Kurland, Brenda F.; Huryn, Donna M.; Wipf, Peter; Herman, James G.
ABSTRACT: Signal Transducers and Activators of Transcription-3 (STAT3), a potent oncogenic transcription factor, is constitutively activated in lung cancer, but mutations in pathway genes are infrequent. Protein Tyrosine Phosphatase Receptor-T (PTPRT) is an endogenous inhibitor of STAT3 and PTPRT loss-of-function represents one potential mechanism of STAT3 hyperactivation as observed in other malignancies. We determined the role of PTPRT promoter methylation and sensitivity to STAT3 pathway inhibitors in non-small cell lung cancer (NSCLC). TCGA and Pittsburgh lung cancer cohort methylation data revealed hypermethylation of PTPRT associated with diminished mRNA expression in a subset of NSCLC patients. We report frequent hypermethylation of the PTPRT promoter which correlates with transcriptional silencing of PTPRT and increased STAT3 phosphorylation (Y705) as determined by methylation-specific PCR (MSP) and real time quantitative reverse transcription (RT)-PCR in NSCLC cell lines. Silencing of PTPRT using siRNA in H520 lung cancer cell line resulted in increased pSTAT3Tyr705 and upregulation of STAT3 target genes such as Cyclin D1 and Bcl-XL expression. We show this association of PRPRT methylation with upregulation of the STAT3 target genes Cyclin D1 and Bcl-XL in patient derived lung tumour samples. We further demonstrate that PTPRT promoter methylation associated with different levels of pSTAT3Ty705 in lung cancer cell lines had selective sensitivity to STAT3 pathway small molecule inhibitors (SID 864, 669 and SID 4, 248, 543). Our data strongly suggest that silencing of PTPRT by promoter hypermethylation is an important mechanism of STAT3 hyperactivation and targeting STAT3 may be an effective approach for the development of new lung cancer therapeutics.